STRATEGIC ANALYSIS OF CAPACITY BUILDING FOR THE CYBER SECURITY OF THE UNITED STATES IN ASIA - Seiko Watanabe (Kajian Asia Pasifik, 2020)
In recent years, cyber-attacks in virtual spaces have been rapidly increasing, and modern centralized states have proven to be incapable of effectively responding to cyber-attacks on their own. To resolve cyber issues, the United States has started cooperating with allied countries such as Japan and the ASEAN countries through Capacity Building (CB). Cyber-attacks include online and physical infrastructures, often referred to as electronic warfare and “hybrid wars.” In this paper, I show the importance of revisiting deterrence theory for cyber security issues. Deterrence theory derives from a traditional International Relations (IR) theory, realism, which emphasizes that states always act to maximize military power. However, in explaining the CB in cyberspace, key concepts and different theoretical frameworks which both scholars of liberalism and neoliberalism advocate, must be incorporated because not only military power, but also economic power has to be taken into account. This paper takes the United States as one case in which infrastructural support in cyberspace is observed. More specifically, I argue that in order for CB to happen, cooperation in cyberspaces must emerge, especially in the realm of economy, legislation, and military support to allied countries. This paper intends to determine the utilities of cyber CB. To do so, I collected data from more than 200 countries and inspected the correlations between cyber-attacks and CB using statistical software R. I also examines other factors such as Internet population, GDP growth rate, war expenditures, economy, military, and law regimes, to determine which are statistically significant in mitigating cyber-attacks. Keywords: cybersecurity, international relations, realism, liberalism, capacity building